2022
DOI: 10.3389/fgene.2022.886781
|View full text |Cite
|
Sign up to set email alerts
|

Time-series transcriptome analysis identified differentially expressed genes in broiler chicken infected with mixed Eimeria species

Abstract: Coccidiosis caused by the Eimeria species is a highly problematic disease in the chicken industry. Here, we used RNA sequencing to observe the time-dependent host responses of Eimeria-infected chickens to examine the genes and biological functions associated with immunity to the parasite. Transcriptome analysis was performed at three time points: 4, 7, and 21 days post-infection (dpi). Based on the changes in gene expression patterns, we defined three groups of genes that showed differential expression. This e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous studies showed that cytokine-cytokine receptor interaction pathway was associated with Eimeria infection ( 29 , 36 ). Of the DEGs enriched in this pathway, IL22RA1, IL1R2 and IL20RA are implicated in immune or inflammatory responses ( 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that cytokine-cytokine receptor interaction pathway was associated with Eimeria infection ( 29 , 36 ). Of the DEGs enriched in this pathway, IL22RA1, IL1R2 and IL20RA are implicated in immune or inflammatory responses ( 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that T. gondii infection could modulate host cell apoptosis through ER stress ( 26 28 ). Notably, ER stress is also associated with E. tenella infection ( 29 ). The DEGs enriched in protein processing in the endoplasmic reticulum pathway included HSPA2, HSPA8, HSP90AA1 and HSPH1, which are the immune-related genes ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…To uncover candidate genes and biological pathways underlying the immune response to disease, researchers have investigated changes in gene expression [11][12][13]. RNA sequencing technology has enabled comprehensive examinations of gene expression across the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined chicken coccidiosis to develop antibiotic alternatives [14,15] and effective anticoccidial vaccines [16,17], and identified candidate genes associated with immune function [11,18]. Previously, our research team identified chronological changes in gene expression patterns throughout the genome in the cecum of broilers affected by coccidiosis, thereby elucidating key responses and pathways [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation